Pocket companion for physical examination and health assessment - Jarvis, Carolyn (Saunders, 2004)
Pocket Companion for Physical Examination and Health Assessment, 4th edition, is a convenient and portable clinical tool for carrying out a holistic, head-to-toe assessment. This handbook is useful either as an adjunct to the Jarvis text, or as an independent primer of basic assessment skills. The Pocket Companion features all the essentials: health history points, exam steps for each body system, normal versus abnormal findings; integrated life span and transcultural considerations; and over 100 meticulously prepared color illustrations. All of this is presented in an attractive and user-friendly format that mirrors the core text. Revised and updated to match the text, the Pocket Companion is cross-referenced to the text by page number for those times when the reader needs more detailed information.